Chris Poldoian os Thomas Diafoirus, Dan Casey as Argan, and Gregory James Berney as Monsieur Diafoirus in 'The Imaginary Invalid' (Tufts Archival Research Center, 2008)
Directed by Sarah Ullman. Production dates were 2009-11-19 to 2009-11-21.